Frauds and fakes in the Australian Aboriginal art market - Alder, Christine (Crime, law and social change, 2011)
This article examines the topic of problematic art in the Australian Aboriginal art market. For Aboriginal people art plays an important social, economic and political role. It has also become a major source of income for many. Thus when the integrity of that art is challenged by allegations of fraud and deception it is imperative to explore the veracity of these claims and the responses made to them. In the article particular attention is devoted to those responses made through both the Australian criminal and civil systems of justice. This analysis shows that there are special problems associated with establishing the authenticity of Aboriginal works of art which tend to hamper the prosecution of fraud cases while a dearth of expertise and interest in art fraud at large among Australian law enforcement bodies is a further barrier to effective action. The conclusion is reached that at present the Australian legal system is poorly equipped to deal with frauds and fakes in the Indigenous art market—a situation which will take time and more imaginative solutions to remedy.